Phase-mismatching dependence of four wave mixing effect in semiconductor optical amplifiers - Kharraz, Osayd M.; M. J., Connelly; M. Supa'at, Abu Sahmah; Abas, Ahmad Fauzi; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir (Optica Publishing Group, 2020)
The phase-mismatch effect due to polarization-dependent mode confinement factor has been shown to be not a crucial problem in semiconductor optical amplifiers (SOAs) and is usually not accounted for. The phase-mismatch four-wave mixing (FWM) process in SOA devices is experimentally reported. The results reveal a sinc-like behavior in the intensity of FWM conjugate as a function of wavelength separation between transverse electric (TE)/transverse magnetic (TM) pumps due to induced confinement factors difference. Efficient FWM occurred for a detuning shift of about 500 GHz, limited by phase-mismatch conditions and determined by coherence length required for low and high frequencies to complete a full phase-match cycle. Phase-match FWM with an infinity coherence length can be fulfilled by proper alignments of co-polarized TE/TM modes of input waves with respect to the birefringent axes of the device structure.